Ageing, the Body and the Gender Regime : Health, Illness and Disease Across the Life Course. - Pickard, Susan; Robinson, Jude. (Milton : Routledge, 2019)
The current (postfeminist) gender order comprises a highly complex coexistence of old and new norms and expectations, freedom and constraints, within a neoliberal social order underpinned by individualism and involving a shift in gender performance by men and women. Health, illness and disease at different points in the life course can be used as a vehicle to illuminate structural and cultural inequalities that persist despite several decades of progressive reform in western countries. This collection brings together a number of key researchers, both established and new to the field, and based across North America, Australia, the UK and Europe, and comprises both empirical and theoretical work. Drawing on a wide range of disciplinary fields, including medical sociology, medical anthropology, nursing, gender studies, sociology of risk and age studies, all authors use heath, well-being, illness and disease as a lens through which to explore the complexities and inequalities associated with late modernity. This book will be of interest to scholars and students of age studies, medical sociology and anthropology, gender studies, healthcare and nursing.
Key theory and the role of genderRecognising dementia, sustaining self; Talk and body talk; Making decisions, having a say; Conclusions; References; 7. 'Men are not women': Biomedicine and the (hetero)sexing of ageing bodies; Romancing successful ageing; Diagnosing discontents; 'Men are not women': differentiating the 'ageing male'; Meanwhile, back at the lab: heterosexualising difference; (Hetero) sex as health; Conclusions; References; 8. Toward an intersectional approach to health in later life: Incorporating age relations; An intersectional approach
Intersectionality in research on health in later life
OCLC-licensed vendor bibliographic record.
Keywords: Aging; Health; SOCIAL SCIENCE -- Feminism & Feminist Theory; SOCIAL SCIENCE -- Gender Studies; HEALTH & FITNESS -- Health Care Issues